Heavy flavours - Buras, A. J.; Lindner, M. (Advanced series on directions in high energy physics, 1992)
This volume is a collection of review articles on the most outstanding topics in heavy flavour physics. All the authors have made significant contributions to this field. The book reviews in detail the theoretical structure of heavy flavour physics within the Standard Model and its confrontation with existing experimental data. The physics of the top quark and of the Higgs play an important role in this volume. Beginning with radiative electroweak corrections and their impressive tests at LEP and hadron colliders, the book summarizes the present status of quark mixing, CP violation and rare de.